Strategic plan for Textile S.A. - Fajardo Piñan, Victor Jose (2019)
The purpose of this thesis is to present the Strategic Plan 2019 to 2024 of the company Textile S.A., including an exhaustive review of its mission, vision, values, and code of ethics. This Strategic Plan will become the guiding light for Textile S.A. to be recognized as a relevant regional player in the textile and confection sector. This Strategic Plan was formulated using D`Alessio´s Sequential Model of the Strategic Process (2015), which included an exhaustive analysis of internal and external factors, and competitive analysis of Peru and of the company. The internal and external analysis resulted in the identification of opportunities, threats, and weaknesses associated with the company. The competitive analysis resulted in the identification of competitive advantages of Peru, and the company and the critical success factors to compete in the textile and confection sector. Textile S.A. can take advantage of the opportunities in the market, the new trends (ecofriendly and e-commerce), and favorable access to raw material in Peru. At the end of the analysis, sixteen strategies were established and ten retained strategies to make the long-term objectives included the developing of new relationships with potential clients in countries where free trade agreements apply, increasing loyalty of current customers to differentiate from competitors, positioning the company´s brand in the local market aiming a mid-high income segment with the clothing design, among others. The success in the implementation and execution of those strategies will depend on the attitude and position taken by the shareholders of the company.